Behavioral Science and COVID-19 : An Interactive Solutions Guide for Better Policy Design - Lim, JungKyu Rhys (Washington, DC: World Bank, 2022)
The first Coronavirus (COVID-19) cases were reported in December 2019 (WHO, 2020). Governments around the world have tried various interventions to stop the COVID-19 spread and encourage vaccination. With growing evidence of the governments’ COVID-19 efforts to deal with the pandemic, this guide aims to summarize interventions and applications, and their effectiveness to address the following three COVID-19 topics: How to reduce COVID-19 spread; How to encourage people to get vaccinated; and How to address misinformation and fake news.